Simulación numérica de las formaciones caballos y Villeta del campo loro, cuenca del putumayo (2010)
For the development of the simulation of the Caballos and Villeta’s Formation in the Loro Field it was necessary to make a new petrophysics interpretation in each one of wells to obtain the Net to Gross, the effective porosity and the absolute permeability, which defined the static model of the simulation; the dynamic model settled down from the load of the historical production of the Field, the curves of relative permeability for each formation, the pressure to the datum, the depth of the oil – water contact, the definition and size of the aquifers and the mechanical states of each one of wells.